The Role of Gender and Friendship Quality on Happiness Among Adolescents in Bandar Lampung - Annisa, Nabila Indi; Lutfianawati, Dewi; Putri, Asri Mutiara (Seurune : Jurnal Psikologi Unsyiah, 2025)
Adolescence is a crucial transitional phase with significant physical, emotional, social, and psychological changes. Studying happiness during this time is important, as adolescents' emotional well-being heavily depends on their social relationships, particularly friendships and gender influences. This topic is increasingly relevant due to rising social, academic, and digital pressures that can enhance or undermine happiness. Exploring adolescent happiness provides insights for improving mental health and laying a foundation for adult well-being. Happiness drives individuals to engage in positive behaviors. This study investigates how gender and friendship quality impact adolescent happiness and examines other related factors. Conducted with 200 participants aged 18 to 21 uses the Authentic Happiness Inventory (AHI) measure for friendship quality. The hypothesis is assessed via multiple regression analysis, revealing that the connection between gender and friendship quality accounts for 8.7% of variance in adolescent happiness, while 91.3% is linked to unexamined factors